O número de ouro e suas belezas - SOBRINHO JUNIOR, Jose Xavier (2019)
This paper aims to make a larger number of math students know the gold number and show the gold value it has, as many do not know it yet. With this objective is that this work is developed, showing the importance of this number present in various aspects of our daily lives, contextualizing it with current records and identifying it mainly in nature. And why the terminology "gold number"? According to information on the schoolkids website, "The golden number is the mathematical representative of perfection in nature." Saying which number is considered gold may be easy, but explaining how mathematicians discovered this number is one of the specific objectives we will answer in the development of this paper. It has been studied since antiquity and many Greek constructions and artistic works present it as a basis. The gold number is represented by the Greek letter Φ (phi) and its value corresponds to 1.61803399 ... But why is this number so important? Why is it so used in buildings, works of art, being the reference of beauty? Because it represents the perfection and beauty of nature, it is present almost everywhere, in nature, in objects and constructions that we consider the most beautiful. Through the numerical sequence discovered by Fibonacci, and later the creation of the Fibonacci Spiral, described in this paper, we understand that the golden number is synonymous with perfection and beauty because it is present in most Divine creation.